Risk of Teenager Pregnancy in Adverse Neonatal Outcome: A Hospital Based Case-Control Study - Ara, Rumi Farhad; Alam, Jahangir (Journal of Current and Advance Medical Research, 2018)
Background: Teenage pregnancy is a risk of adverse neonatal outcome. Objective: The purpose of the present study was to estimate the risk of teenage pregnancy in the adverse neonatal outcomes. Methodology: This case-control study was conducted in the Department of Obstetrics and Gynecology at Dhaka Medical College & Hospital, Dhaka, Bangladesh and Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh from April to July 1999 for a period of four (4) months. The teenage mothers with the age group of 11 to 19 years who were admitted in the study period was selected as case and pregnant women with the age group of more than 19 years were selected as control group. Perinatal mortality rate was calculated by foetal death after 28 weeks of gestation up to death within one week of delivery per 1000 live births. At birth, babies were examined for any congenital malformation. Gestational age of infants was assessed by Perkins' scoring system. Babies were assessed by Apgar score at l and 5 minutes. Result: A total number of 100 pregnant mothers were recruited for this study of which 50 pregnant mothers were in the case group and the rest 50 mothers were in the control group. Thirty-two babies of teenage mothers were asphyxiated at birth and 56.0% were healthy. At 1 minute, 52.0% babies of teen mothers have more than 7 Apgar score, whereas 86.0% babies born to non-teen mothers showed a Apgar score more than 7 which was also a significant difference. Among the cases, 54.0% babies have birth weight >2.5 kg. On the other hand, 72.0% of babies of non-teen mothers have birth weight >2.5 kg. Higher rate of perinatal morbidity in terms of birth asphyxia, prematurity, intrauterine growth retardation (IUGR), jaundice and septicaemia was found among the neonates of teen mothers than non-teen mothers. Conclusion: In conclusion birth asphyxia, prematurity, intrauterine growth retardation, jaundice and septicaemia are most commonly found among the neonates of teen mothers than non-teen mothers. Journal of Current and Advance Medical Research 2017;4(2):44-47